PENERAPAN METODE DISKUSI DENGAN BANTUAN MEDIA ANIMASI UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR MATA DIKLAT MOTOR SISTEM BAHAN BAKAR SISWA KELAS XI SMK MUHAMMADIYAH GAMPING TAHUN AJARAN 2014/2015 - Rico Harry Prasetyo; Rabiman Rabiman (Universitas Sarjanawiyata Tamansiswa, 2015)
The purpose of this study was to improve the activeness and learning outcome of class XI TKR students of SMK Muhammadiyah Gampingin the academic year of 2014/2015 by applying the discussion method with assist media of animation on the Engine Fuel System subject.This study was a classroom action research conducted by applying the discussion method with assist media of animationin SMK Muhammadiyah Gamping in the academic year of 2014/2015. There were 28 students as the subjects of this study. This study was conducted in three cycles, in which every cycle consisted of four stages: planning, implementation of action, observation, and reflection. The techniques applied in collecting data were observation sheet to measure the students’ learning activeness, and the instrument of test in the form of multiple choice questions divided into pre-test and post-test to measure the improvement of the students’ learning outcome.The result showed that the application of the discussion method with assist media of animation could increase the students’ activeness and learning outcome in the Engine Fuel System subject of class XI SMK Muhammadiyah Gamping. It could be seen from the average number of the students’ activeness on cycle I that was 42,85%, increased to 48,72% on cycle II, then itreached up to 57,64% on cycle III. Mean while, the average number of the learning outcome on cycle I was 43,92 with the lowest score of 35, the highest score of 75, and there were only two students who passed the minimum completeness criteria KKM. The average number increased on the cycle II, reaching up to 65,35 with the lowest score of 55, the highest score 75, and seven students passed the KKM. Then, on cycle III, it increased again to the number of 76,25 with the lowest score of 65, the highest score of 85, and 25 out of 28 students passed the KKM. Thus, it can be concluded that the application of the discussion method with assist media of animation can improve the students’ activeness and learning outcome in the Motor Fuel System subject of class XI SMK Muhammadiyah Gamping.